حوکمرانى دروست دەروازەیەک بۆ چەمک و کارەکتەر و ئامرازەکانى - رسول, عابد خالد; محمدامین, پێشرەو على (Sulaimani Journal for Humanities, 2018)
There are many indications that the concept of good governance is mentioned in many of the literature on development, especially in the field of institutional, human and administrative and others. Good governance, in its general sense, indicates a number of practices and methods that guarantee the achievement and support of human welfare. Human opportunities and opportunities, and open up multiple perspectives for them to achieve a better standard of living on all levels of life, including the economic, social, political and security aspects. The mechanisms of good governance mean the existence of the fundamentals of governance such as: accountability, equality, participation, transparency, and the ability to adapt to and respond to different variables, although there are many criteria set by the United Nations Development Program, which reach up to nine mechanisms. That all of them important to improving governance in public or privet sectors.